Program Corporate Social Responsibility (CSR) dan Strateginya Untuk Peningkatan Kepuasan Masyarakat Serta Dampak Sosial Ekonomi Masyarakat - Arsyad, Apendi; Sudarijati, Sudarijati; Gemina, Dwi (Universitas Djuanda, 2017)
The purpose of this research was to determine the effect of the perception and satisfaction of the community to CSR and its impact on socioeconomic in Bogor regency. Questionnairewere distributed to 250 respondents . Likert scale was used prior to testing with multiple regression. The results showed that the implementation of CSR programs in Bogor has been done quite effectively. Perception and satisfaction of the community have an influence simultaneously and partially on CSR. The CSR activities in education, health , environment , increasing of desire and basic human needs and security simultaneously have influences towards the socio-economic communities. Partially, education has no effect on socioeconomic condition. The implementation strategy of using Importance Performance Analysis ( IPA ). The strategies which have been generated are 1 ) making ongoing improvements so that the performance attributes ( CSR programs expectancy ) will be increased ; 2 ) maintaining so that the performance will not be declined; 3 ) should be managed seriously because community usually can lead to a disappointment ; 4 ) evaluating all activitiesKeywords : CSR program, Community Satisfaction and Social Economic of the community